Associations between trajectories of cardiovascular risk factor change and cognitive impairment in Chinese elderly: A nationwide cohort study - Duan, Xinyu; Dang, Yusong; Kang, Chenxi; Rong, Peixi; Yan, Mingxin; Zhang, Shutong; Cui, Jing; Zhao, Yaling; Chen, Fangyao; Zhou, Jing; Wang, Duolao; Pei, Leilei (Frontiers in Aging Neuroscience, 2023)
Objectives: This study aimed to investigate the relationship between long-term trajectories of changes in cardiovascular risk factors (CVRFs) and the risk of cognitive impairment among Chinese adults over 60 years old. Methods: Data were obtained from the Chinese Longitudinal Healthy Longevity Survey 2005-2018. Cognitive function was evaluated longitudinally through the Chinese version of the Mini-Mental State Examination (C-MMSE), and cognitive impairment (C-MMSE ≤ 23) was used as the main outcome variable. The cardiovascular risk factors, including systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), pulse pressure (PP), and body mass index (BMI), were continuously measured in the follow-up duration. The patterns of trajectories of changes in CVRFs were derived from the latent growth mixture model (LGMM). The Cox regression model was used to evaluate the cognitive impairment hazard ratio (HR) across different CVRF trajectories. Results: A total of 5164 participants aged ≥ 60 years with normal cognitive function at baseline were included in the study. After a median follow-up of 8 years, 2071 participants (40.1%) developed cognitive impairment (C-MMSE ≤ 23). The four-class trajectories of SBP and BMI were obtained by means of LGMM, and the trajectories of DBP, MAP, and PP were grouped into a three-class subgroup. In the final adjusted Cox model, the lowered SBP [adjusted HR (aHR): 1.59; 95% CI: 1.172.16], lowered PP (aHR: 2.64; 95% CI: 1.664.19), and progressively obese (aHR: 1.28; 95% CI: 1.021.62) and stable slim (aHR: 1.13; 95% CI: 1.021.25) were associated with the higher risk of cognitive impairment. Low stable DBP (aHR: 0.80; 95% CI: 0.660.96) and elevated PP (aHR: 0.76; 95% CI: 0.630.92) decreased the risk for cognitive impairment among participants. Conclusions: Lowered SBP, lowered PP, progressive obesity, and stable slim increased the risk for cognitive impairment in the Chinese elderly. Low stable DBP and elevated PP were protective against cognitive impairment, but more DBP lowering and ≥ 25 mmHg growth in PP contributed to a higher risk of cognitive impairment. The findings have important implications for preventing cognitive impairment in elder adults based on the long-term trajectories of changes in CVRFs.